Antigone’s Phallus Envy and Its Comparison to Indonesian Dramas’ Characters: A Freudian Perspective - Dina Amelia (English Department, Faculty of Humanities, Andalas University, 2021)
Antigone’s character has developed phallus envy. Phallus envy seems to also appear in the Indonesian dramas Djinak-Djinak Merpati and Kami, Perempoean which were written during the Japanese colonialization in Indonesia. Freudian perspective, in this case, Freudian psychoanalysis helps to scrutinize the characters in the dramas. This research is to present and elucidate Antigone’s phallus envy and its comparison to Indonesian dramas by applying Freud’s Id, Ego, and Superego. The qualitative method is applied based on the theory used. Antigone’s phallus envy is the result of her traumatic past experiences as well as the stereotype and position of women in the ancient Greek era. Similar to the characters from the Indonesian dramas, Moerni, Sri, and Aminah. The causes of their phallus envy are emphasized on the stereotype of women in Indonesia during Japanese colonization that influences the way they think and behaves toward the people around them, especially men.